2022
DOI: 10.3390/microorganisms10102059
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Bacterial Community Structure, Diversity, and Chemical Properties in the Rhizosphere Soil on Fruiting-Body Formation of Suillus luteus

Abstract: Mycorrhiza helper bacteria (MHB) play an important role in driving mycorrhizal formation. There are few reports on the relationship between bacteria and fruiting growths. Taking mycorrhizal rhizosphere soil from sporocarps of the S. luteus and non-mycorrhizal rhizosphere soil of the host plant (Larix gmelinii), we measured the bacterial community structure and diversity and chemical properties to clarify the effect of bacteria on fruiting-body formation. The bacterial diversity was significantly higher in myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…A negative correlation between CTC, V%, Ca2+, Mg2+ and Acidipila-Silvibacterium was found in our results. In the study by Zhou et al , Acidipila-Silvibacterium presented a positive and negative presentation with K, P and N. Although in our study we did not evaluate P and N, the result for nutrient K corroborated this, indicating that this group of bacteria has a potential relationship with soil nutrients [ 75 ]. Regarding the negative correlation of CEC and V% with the genus Geothermomicrobium , a genus broadly found in soils, our study is the first that shows the correlation between this bacterium and the macro and micronutrients present in the soil of grapevines [ 76 ].…”
Section: Discussionsupporting
confidence: 71%
“…A negative correlation between CTC, V%, Ca2+, Mg2+ and Acidipila-Silvibacterium was found in our results. In the study by Zhou et al , Acidipila-Silvibacterium presented a positive and negative presentation with K, P and N. Although in our study we did not evaluate P and N, the result for nutrient K corroborated this, indicating that this group of bacteria has a potential relationship with soil nutrients [ 75 ]. Regarding the negative correlation of CEC and V% with the genus Geothermomicrobium , a genus broadly found in soils, our study is the first that shows the correlation between this bacterium and the macro and micronutrients present in the soil of grapevines [ 76 ].…”
Section: Discussionsupporting
confidence: 71%
“…Changes in soil physicochemical properties caused by fire disturbances may lead to the disappearance of or a reduction in certain fungal species in the soil, and this affects the alpha diversity of soil fungi [51]. In some studies, MC, AP, AK and TN were found to correlate with changes in the alpha diversity of soil fungi [52,53]. In our study, the differences in the soil physical and chemical properties of the fire sites did not change the total number of soil fungal species in this study, which is in line with the results of others [51].…”
Section: The Effects Of Fire Disturbance On Fungal Alpha Diversitymentioning
confidence: 99%
“…The mycorrhizal system is well known for its rich diversity of microorganisms within its associated microbiomes ( van der Heijden et al., 2015 ; Shi et al., 2023 ), which makes it an intriguing subject of research. The previous study of S. luteus -related biodiversity was mainly focused on the bacteria characterization ( Bending et al., 2002 ; Zhou et al., 2022 ), however, another layer of complexity contributed by mycoviruses infecting S. luteus remains unknown. Therefore, further research on mycoviruses associated with S. luteus is warranted.…”
Section: Introductionmentioning
confidence: 99%